Quelques propos sur le logarithme et le decibel - Maurin, Michel (Canadian Acoustics, 1999)
It is very trite and classical to use decibels in acoustics, but when one looks in detail this definition may call us for several historical and methodological points, and more may render us puzzled. All of this because decibels are based upon logarithm function in order to define levels from adimensional ratios, and because there are many different ways in order to explain the presence of logarithm. The paper gives a short recall of logarithm properties and investigate the mean reasons, in mathematical and physical fields, in human and environmental sciences also. The conclusion is rather severe about the revelancy of Fechner law in Psychophysics, while very pregnant in decibels and levels definition.